PENGARUH UKURAN PERUSAHAAN, PRICE EARNING RATIO DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN (Studi Empiris Pada Perusahaan Aneka Industri yang Terdaftar di Bursa Efek Indonesia tahun 2011 - 2015) - Henriansyah, Galih; Dharmayuni, Lita (EQUITY, 2017)
The purpose of this study is to know the influence ofFirm Size, Price Earning Ratio, and Profitability to Firm’s Value in various industry companies listed in Indonesia Stock Exchange 2011-2015. The data in this research is secondary data obtained through the company's annual financial statements for the financial period ended 2011-2015. This study used 7 samples of various industry companies listed on the Indonesia Stock Exchange. Each company is a company that has published its financial statements and complete data regarding the variables that will be examined during the period 2011-2015. The sample is taken by using purposive sampling, that the selection of members of the sample based on certain criteria. The results showed that the influence of Firm Size and Price Earning Ratio are positive and not significant to the Firm’s Value, and the influence of Profitability are positive and significant to on the Firm’s Value.